Local area networks : architectures and implementations - Martin, James; Chapman, Kathleen Kavanagh;Leben, Joe (Englewood Cliffs, New Jersey : Prentice-Hall, 1994)
Offers readers an authoritative, in-depth exploration of the local area network. This book incorporates the latest technology, protocols, techniques, and hardware and software employed in computer networking
1. Local Area Networks -- I. LOCAL AREA NETWORK CONCEPTS -- 2. Physical Transmission -- 3. Medium Access Control -- 4. Network Architectures -- 5. Networking Software -- II. LOGICAL LINK CONTROL 6. Local Area Network Architecture -- 7. LLC Service Definition -- 8. LLC Protocol Specification -- 9. LLC Implementations -- III. MEDIUM ACCESS CONTROL -- 10. CSMA/CD (Ethernet) -- 11. The Ethernet Version 2 Specification -- 12. Token Bus -- 13. Token Ring. -- 14. Fiber Distribution Data Interface -- 15. Apple LocalTalk -- IV. ENTERPRISE INTERNETWORKING -- 16. The Internetworking Environment -- 17. Protocols for Internetworking -- 18. Heterogeneous Internetworking -- 19. Bridges -- 20. Routers -- V. NETWORKING SOFTWARE -- 21. IBM and Microsoft Networking S0oftware -- 22. Novell NetWare -- 23. TCP/IP -- 24. AppleTalk.
Includes index.
Keywords: LOCAL AREA NETWORKS (COMPUTER NETWORKS)